Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2012
DOI: 10.1145/2207676.2208396
|View full text |Cite
|
Sign up to set email alerts
|

"Watts in it for me?"

Abstract: The design of technological interventions to motivate behaviour-based reductions in end-user energy consumption has recently been identified as a priority for the HCI community. Previous interventions have produced promising results, but have typically focused on domestic energy consumption. By contrast, this paper focuses on the workplace context, which presents very different opportunities and challenges. For instance, financial consequences, which have proved successful as motivations in the domestic enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(19 citation statements)
references
References 22 publications
1
17
1
Order By: Relevance
“…Such link is most likely rather specific to public sector organisations like Southshire Council (especially in a time of severe job cuts), but it is interesting nonetheless. It contrasts with previous research that suggests that employees (of a profitmaking company) do not believe that they may gain personal financial benefits from reduced workplace energy costs [22,17].…”
Section: Policy and Communicationcontrasting
confidence: 66%
See 1 more Smart Citation
“…Such link is most likely rather specific to public sector organisations like Southshire Council (especially in a time of severe job cuts), but it is interesting nonetheless. It contrasts with previous research that suggests that employees (of a profitmaking company) do not believe that they may gain personal financial benefits from reduced workplace energy costs [22,17].…”
Section: Policy and Communicationcontrasting
confidence: 66%
“…to a distant manager) [37]. Foster et al conducted workshops with a range of staff to explore perceptions of energy use in the workplace, also emphasising the need for workplace interventions to be particularly sensitive to specific organisational cultures [17]. Through a set of interviews Castelli et al note that there are differences between industrial and office-based work settings [7], and propose that enterprise information systems should present energy consumption information according to different users' roles.…”
Section: Related Workmentioning
confidence: 99%
“…On the one hand, automation systems have proven to reduce electricity requirements in many real‐world scenarios, as depicted in the previous sections. However, several findings suggest that employees of an organization may find automated interventions unfavorable, particularly when they intervene in their daily working tasks.…”
Section: Persuasion Approach—initial Methodology and Next Stepsmentioning
confidence: 99%
“…Our secondary goal was to contribute research that helps to decrease the research gap formulated by Foster, Lawson, Wardman, Blythe and Linehan (2012). The authors identified a "research knowledge gap present in understanding the end--users of energy in the workplace and, therefore, the design of appropriate and achievable workplace energy interventions, particularly those that encompass novel ways of encouraging people to adopt positive energy usage behaviour whilst at work."…”
Section: Introductionmentioning
confidence: 99%